Cocoa Bean Hulls: Effect on Nutritional Quality, Texture and Sensory Properties of Pound Cake - Elif Öztürk; Gülden Ova (Turkish Journal of Agriculture: Food Science and Technology)
In this study, wheat flour was substituted with the following ratios of the raw (RCBH) and leached (LCBH) cocoa bean hull (CBH) in pound cakes (PC) (CBH/wheat flour ratios: 20/80 (20%), 30/70 (30%) and 40/60 (40%)), respectively. The proximate composition and the content of bioactive compounds in the cake samples for each weight ratio of RCBH and LCBH and in the hulls were evaluated. Fiber, ash, total antioxidant activity (TAA) and total phenolic compound (TPC) contents increased with the CBH content in the cakes. No significant difference was found in the specific volume among the cake samples. Based on the results of the textural analysis, all cake samples showed higher hardness, lower springiness and cohesiveness than those of the control cake. Regarding to the color of the crumb and crust, the 40% LCBH and RCBH cakes presented the lowest L*, a* and b* values. According to the Principal Component Analysis (PCA), it was observed that the properties with respect to the cell uniformity, adhesiveness, sweetness, oiliness and humidity of the 20LCBH and 20RCBH cakes can be distinguished clearly from the other flour substituted cakes.